The Application of the Burden of Proof Concept in Indonesia: A Comparative Study - Abdullah, Abdullah; Hatta, Muhammad (SASI, 2022)
Introduction: One of the reasons for a reverse proof system is the difficulty of proving the offenses committed by certain perpetrators of a criminal offense, such as corruption and money laundering. Thus, the government issues the legal policy to apply a reverse burden of proof to solve this problem.Purposes of the Research: This study aims to analyze the application of the reverse burden of proof in Indonesian and Islamic criminal law.Methods of the Research: This research is legalistic, doctrinal, or normative, using a comparative law approach to compare the application of a reverse burden of proof in Indonesian criminal law and Islamic criminal law.Results of the Research: The application of a reverse burden of proof in Indonesia is limited and balanced (balanced probability of principles) as regulated in Article 37 of Law no. 31 of 2019 in conjuction with Law No. 20 of 2000 concerning the Eradication of Corruption Crimes and Article 35 of Law no. 8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering. In Islamic criminal law, the application of t a reverse burden of proof has long been carried out, as seen in Surah Al-Nisa verse 135 and the story of Prophet Yusuf's proof of Zulaikha's accusation in Surah Yusuf verses 24-29, and several hadiths of the Prophet Muhammad. These two legal systems are similar in terms of the application of a reverse burden of proof that is only applied to certain cases, such as corruption and money laundering. However, the difference is that the application of a reverse burden of proof in Indonesian criminal law is limited and balanced. In contrast, the principle of a reverse burden of proof against corruption cases in Islamic criminal law is absolute.